Prospective association of morning salivary cortisol with depressive symptoms in mid-life: a life-course study. - Marie-Claude Geoffroy; Clyde Hertzman; Leah Li; Chris Power (PLoS ONE)
Objective Associations of cortisol and depression vary at different life-stages, yet population-based, prospective studies are scarce. We aimed to assess associations of morning cortisol with depressive symptoms in mid-life taking account of lifetime psychological health. Methods Participants were 5,403 men and women from the 1958 British Birth Cohort whose salivary cortisol was assessed at 45y (45min after waking (T1) and 3h later (T2)) and who completed the 5-item Mental-Health Index (MHI-5) about depressive symptoms at age 50y. Lifetime psychological health was identified from child and adult measures. Results For women, higher T2 cortisol at 45y predicted depression (MHI-5 scores ≤52) at 50y (odds ratio [OR]=1.17; 95% confidence intervals [CI] 1.05,1.30 per standard deviation increase in T2 cortisol), attenuating when adjusted for current (45y) and previous (7-42y) psychological health (OR=1.11; 95% CI 0.98, 1.24). Similarly, an association in women of flatter cortisol delta (T2-T1) with depressive symptoms at 50y weakened after adjustment for current (45y) and previous (7-42y) psychological health. For men, lower T2 cortisol at 45y predicted greater depressive symptoms at 50y and the association strengthened when adjusted for lifetime psychological health. Likewise, lower cortisol AUC predicted higher risk of depression for men after adjusting for prior psychological health (OR=0.85; CI 0.72, 1.00). Associations were largely unaltered by control for covariates. Conclusions In women, higher cortisol in late morning at 45y is prospectively associated with depressive symptoms at 50y through a link with lifetime psychological health. In men, lower cortisol predicts subsequent symptoms, independent of depressive history.